Polyester-Based Dendrimer Nanoparticles Combined with Etoposide Have an Improved Cytotoxic and Pro-Oxidant Effect on Human Neuroblastoma Cells - Silvana Alfei; Barbara Marengo; Cinzia Domenicotti (MDPI AG, 2020)
Etoposide (ETO) is a cytotoxic drug that exerts its effect by increasing reactive oxygen species (ROS) production. Although ETO is widely used, fast metabolism, poor solubility, systemic toxicity, and multi-drug resistance induction all limit its administration dosage and its therapeutic efficiency. In order to address these issues, a biodegradable dendrimer was prepared for entrapping and protecting ETO and for enhancing its solubility and effectiveness. The achieved dendrimer complex with ETO (CPX 5) showed the typical properties of a well-functioning delivery system, i.e., nanospherical morphology (70 nm), optimal Z-potential (−45 mV), good drug loading (37%), very satisfying entrapment efficiency (53%), and a remarkably improved solubility in biocompatible solvents. In regards to its cytotoxic activity, CPX 5 was tested on neuroblastoma (NB) cells with very promising results. In fact, the dendrimer scaffold and ETO are able to exert per se a cytotoxic and pro-oxidant activity on human NB cells. When CPX 5 is combined with ETO, it shows a synergistic action, slowly releasing the drug over time and significantly improving and protracting bioactivity. On the basis of these findings, the prepared ETO reservoir represents a novel biodegradable and promising device for the delivery of ETO into NB cells.